PENGARUH REKRUTMEN SELEKSI DAN PENEMPATAN KARYAWAN TERHADAP KINERJA FRONTLINER PADA BANK BNI KANTOR CABANG SALATIGA - Saela Meiyer (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
The achievement of frontliner performance at the Bank BNI Salatiga Branch Office during the last three years has not been optimal and has even tended to decline. Factors that can affect frontliner performance are recruitment, selection and placement of employees. The purpose of this study was to determine the effect of recruitment, selection and placement of employees on the performance of frontliners at the Bank BNI Salatiga Branch Office. The sample in this study was all 30 frontliners of Bank BNI Salatiga Branch Office using saturated sampling method or census because the population is relatively small. The analytical method used is multiple linear regression analysis using the SPSS program. The results showed that the simultaneous and partial recruitment, selection and placement of employees had an effect on performance.